(untitled) (Zaporizhzhia Historical Review, 2021)
In the article the stages of the educational system formation in the South of Ukraine are regarded. The functioning of all the educational links is described, namely the secular and ecclesiastic primary schools, professional schools, the university. The author has analyzed the structure of annual plans, teaching methods, the significance of the teachersí educational work. Pupils and studentsí social and age peculiarities are researched.